Biallelic Variants in MNS1 Are Associated with Laterality Defects and Respiratory Involvement - Rim Hjeij; Joseph Leslie; Hoda Rizk; Bernd Dworniczak; Heike Olbrich; Johanna Raidt; Sebastian Felix Nepomuk Bode; Alice Gardham; Karen Stals; Mohammad Al-Haggar; Engy Osman; Andrew Crosby; et al. (Cells, 2024)
Defects in motile cilia, termed motile ciliopathies, result in clinical manifestations affecting the respiratory and reproductive system, as well as laterality defects and hydrocephalus. We previously defined biallelic MNS1 variants causing situs inversus and male infertility, mirroring the findings in Mns1−/− mice. Here, we present clinical and genomic findings in five newly identified individuals from four unrelated families affected by MNS1-related disorder. Ciliopathy panel testing and whole exome sequencing identified one previously reported and two novel MNS1 variants extending the genotypic spectrum of disease. A broad spectrum of laterality defects including situs inversus totalis and heterotaxia was confirmed. Interestingly, a single affected six-year-old girl homozygous for an MNS1 nonsense variant presented with a history of neonatal respiratory distress syndrome, recurrent respiratory tract infections, chronic rhinitis, and wet cough. Accordingly, immunofluorescence analysis showed the absence of MNS1 from the respiratory epithelial cells of this individual. Two other individuals with hypomorphic variants showed laterality defects and mild respiratory phenotype. This study represents the first observation of heterotaxia and respiratory disease in individuals with biallelic MNS1 variants, an important extension of the phenotype associated with MNS1-related motile ciliopathy disorder.